Numerical study of Balearic meteotsunami generation and propagation under synthetic gravity wave forcing. (March 2017) - Ličer, Matjaž; Mourre, Baptiste; Troupin, Charles; Krietemeyer, Andreas; Jansá, Agusti; Tintoré, Joaquín
Highlights: Meteotsunami generation, amplification and propagation is investigated using synthetic forcing. Contributions of Mallorca shelves and Menorca Channel are quantified for different gravity wave forcing angles and speeds. The Channel is the key build-up region. Shelves do not significantly contribute to substantial oscillations in Ciutadella. Channel bathymetry serves as a focusing lens for meteotsunami waves. Meteotsunami speed under sub- and supercritical forcing is estimated. First order estimate of its magnitude is derived. Abstract: We use a high resolution nested ocean modelling system forced by synthetic atmospheric gravity waves to investigate Balearic meteotsunami generation, amplification and propagation properties. We determine how meteotsunami amplitude outside and inside of the Balearic port of Ciutadella depends on forcing gravity wave direction, speed and trajectory. We quantify the contributions of Mallorca shelves and Menorca Channel for different gravity wave forcing angles and speeds. The Channel is demonstrated to be the key build-up region determining meteotsunami amplitude in Ciutadella while northern and southern Mallorca shelves serve mostly as barotropic wave guides but do not significantly contribute to seiche amplitude in Ciutadella. This fact seriously reduces early-warning alert times in cases of locally generated pressure perturbations. We track meteotsunami propagation paths in the Menorca Channel for several forcing velocities and show that the Channel bathymetry serves as a focusing lens for meteotsunami waves whose paths are constrained by the forcing direction. We show that faster meteotsunamis propagate over deeper ocean regions, as required by Proudman resonance. We estimate meteotsunami speed under sub- and supercritical forcing and derive a first order estimate of its magnitude. We show that meteotsunamis, generated by supercritical gravity waves, propagate with a velocity which is equal to an arithmetic mean of the forcing velocity and local barotropic ocean wave speed.